2018
DOI: 10.21608/ejchem.2018.2927.1270
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and nanotechnology advanced solutions to improve ecofriendly cotton's coloration and performance properties

Abstract: T HIS RESEARCH aims to utilize microwave energy and nanotechnology to improve the printability and performance of cotton prints via screen printing technique. Each cotton sample was individually pre-treated by microwave power ranged from 300 to 700 watts and for a period ranged from 1 to 9 min. Afterwards the optimum sample was printed by printing paste containing Remazol™ reactive dye and silver nanoparticles (Ag-NPs) with different concentrations. The printed samples were fixed using microwave energy then we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Some studies have suggested that healthcare textiles can act as reservoirs and vehicles for the spread of microorganisms in hospitals [ 3 ]. With the development of nanotechnology, some inorganic nanoparticles (NPs), such as silver, copper, and zinc, have been identified as promising candidates in combating pathogenic microorganisms [ 4 , 5 , 6 , 7 , 8 , 9 ]. Nanotechnology-driven therapies with metal and metal oxide nanoparticles (NPs) are emerging as a promising alternative to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have suggested that healthcare textiles can act as reservoirs and vehicles for the spread of microorganisms in hospitals [ 3 ]. With the development of nanotechnology, some inorganic nanoparticles (NPs), such as silver, copper, and zinc, have been identified as promising candidates in combating pathogenic microorganisms [ 4 , 5 , 6 , 7 , 8 , 9 ]. Nanotechnology-driven therapies with metal and metal oxide nanoparticles (NPs) are emerging as a promising alternative to antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…The amazing utilization of microwave energy and nanotechnology to improve the printability and performance of cotton prints via screen printing technique was reported [77]. They pre-treated each cotton sample separately by microwave power in the range of 300 to 700 watts for a period of 1 to 9 min.…”
Section: Sl Nomentioning
confidence: 99%
“…Therefore, high-tech materials and fabric constructions will improve wearer comfort while incorporating distinctive features [ 2 ]. Among natural fibers, cotton is the most popular because of its softness, breathability, safety, low cost, regeneration performance, strength, elasticity, biodegradability, and hydrophilicity [ 3 , 4 ]. Cotton fabric does, however, have some disadvantages, including the possibility of microbial attacks on its fibrous structure, the ease with which creases form, and the loss of mechanical strength [ 5 ].…”
Section: Introductionmentioning
confidence: 99%